'Now I use words like asymmetry and unstable': nurses' experiences in using a standardized assessment for motor performance within routine child health care. Issue 2 (22nd October 2015) - Johansen, Kine; Lucas, Steven; Bokström, Pär; Persson, Kristina; Sonnander, Karin; Magnusson, Margaretha; Sarkadi, Anna
Abstract: Rationale, aims and objectives: There is an increasing recognition that early intervention is important for children with motor disorders. The use of standardized assessment methods within the Swedish Child Health Services (CHS) may improve early identification of these children and thereby their development and quality of care. Given the key role of nurses within the CHS, we explored their experiences of using a structured assessment of motor performance (SOMP‐I) in a clinical setting, and investigated possible barriers and facilitators for implementation of the method within the CHS. Methods: The study was conducted in 2013 in Uppsala County, Sweden. Ten child health nurses participated in two focus group interviews, which were analysed using systematic text condensation. Results: The analysis yielded three themes: (1) increased knowledge and professional pride – nurses described their desire to provide high‐quality care for which SOMP‐I was a useful tool; (2) improved parent–provider relationship – nurses felt that using SOMP‐I involved both the parents and their infant to a greater extent than routine care; and (3) conditions for further implementation – nurses described that the time and effort needed to master new skills must be considered and practical barriers, such as lack of examination space, resource constraints and difficulties in documenting the assessment must be addressed before implementing the SOMP‐I method in routine care. Conclusion: Child health nurses felt that the SOMP‐I method fitted well with their professional role and increased the quality of care provided. However, significant barriers to implementing SOMP‐I into routine child health care were described.